Some of us are looking - O'Connor, Carlene (O'Connor, Carlene. County Kerry mystery., 2023)
When a beautiful young woman named Brigid, part of a ragtag caravan of young people selling wares by the roadside, is brutally murdered after bringing an injured hare to her veterinary practice, Dimpna Wilde helps Detective Sergeant Cormac O'Brien investigate, finding ominous signs everywhere they look.